A conceptual review of risk communication network for protecting immigrant knowledge workers. Issue 2 (12th October 2015) - Oh, Namkyung; Beckett, Julia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to define immigrant knowledge workers (IKWs) as a vulnerable population in the urban emergency management context, and explored how to provide public safety services to IKWs. Due to nomadic features such as high mobility, spatio-temporality, and preferred autonomy, IKWs have difficulties in building required social ties with long-term residents in the urban emergency management system (UEMS). As such, IKWs are easily isolated and become vulnerable to disasters. Design/methodology/approach – This study introduced possible types of network structure, compared each structure's weaknesses and strengths in terms of risk communication, and suggested the strategic use of brokers for effective risk communication with application of network analysis perspective. Findings – This study argued that the current space-based model causes tension in protecting NKWs and suggested the strategic use of brokers for the facilitated risk communication and for the protection of UKWs in more effective ways. The brokers in UEMS should pursue the core values of partnership, participation, and consultation in building mutual supportive channels within UEMS and the brokers should have sufficient cognitive capacity to avoid system fragmentation and collapse. Research limitations/implications – Due to the limitations as conceptual paper, sometimes it lacks empirical data to support the main arguments of this paper. To address this, the authors put that part as a suggestion for future studies. Originality/value – With the strategic use of brokers, UEMS would be more resilient and accountable in providing public safety services to its citizens.